PENGEMBANGAN FILM PENDEK PENDIDIKAN BAHAYA NARKOTIKA DAN ZAT ADIKTIF UNTUK PESERTA DIDIK DI SMKN PERTANIAN 1 SUKARAJA - Permana, Rizky Dwi; Saepuloh, Luthpi; Yudianto, Arif (Jurnal Ilmiah Wahana Pendidikan, 2024)
Learning is basically an effort to build character for students and also teachers involved in the learning process. Most of the teaching staff in Indonesia tend to use conventional media which uses verbal delivery methods. According to Law of the Republic of Indonesia No. 20 of 2003 concerning the National Education System, it is stated that education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence. , noble morals, and skills needed by himself, society, nation and state. The era has developed, therefore the adaptation of students' habits automatically changes to become technology oriented, where they are more interested in things related to technology and things like that. Film is a flexible medium. Initially, film media was used as an audio-visual entertainment medium, where at that time the entertainment used was usually in the form of audio or sound only and also writing, be it magazines, newspapers, comics or the like. However, as the film industry develops in the world, this film has become more flexible, where it can be used simply as entertainment, as a source of motivation, as an outlet for feelings, until finally films can also be used as anti-mainstream learning media. Based on the results of data research from the Ministry of Communication and Information in 2021 in the 2021 BNN Drugs Report, it was explained that narcotics use among teenagers aged 15-35 years reached 82.4% with the status of users, 47.1% with the status of dealers and 31.4% with the role of couriers. . There is also the use of narcotics among pupils and students reaching 27%. The National Narcotics Agency said that there would be an increase in the use of these narcotics by 1.95% in 2022 compared to 2019.